Upaya Pemerintah terhadap Sosialisasi Kerukunan di Sumatera Utara - Tobing, Wirman; Husaini, Alpahmi; Rahman, Rizki Fachru (MODELING: Jurnal Program Studi PGMI, 2023)
Various cases of religious disproportionality, such as the destruction of religious sites, often occur in Indonesia. This is certainly one of the obstacles for Indonesia to become a developed country. Religion is part of Human Rights (HAM) which must be respected and protected. Based on the Constitution of the Republic of Indonesia, the state has an obligation to guarantee religious harmony. Indonesia has officially legalized six official religions. The People's Movement for Human Rights Education launched the concept of Human Rights Friendly Cities in 1997 with the concept of cities that are inclusive, fair and non-discriminatory. The concept was then developed by the World Forum on Human Rights Cities which is held annually in Gwangju, South Korea. The government's role is very influential in maintaining religious harmony, the government has made various efforts, including by issuing laws and regulations and establishing Religious Harmony Forums (FKUB) in various provinces to maintain religious harmony. The research methodology is library research and observation.